2001
DOI: 10.1111/j.1651-2227.2001.tb03257.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of vincristine toxicity by itraconazole in children with lymphoid malignancies

Abstract: Eight consecutive paediatric patients with acute lymphoblastic leukaemia (ALL) (n=7) and T‐cell non‐Hodgkin's lymphoma (NHL) (n=1) presenting within a 5‐wk interval were started on a standard induction protocol which included weekly treatment with vincristine for 4 wk. Itraconazole was commenced as antifungal prophylaxis, 1–21 d after the first injection of vincristine. Within 2 to 4 wk, enhanced vincristine neurotoxicity was noted in all patients, abdominal cramps and constipation occurred most frequently, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The first hyponatremic episode in our ALL cohort started on average between days 27 and 28 (average day 27.6) but occurred earlier or later in some patients (range from day 12 to day 39 after start of therapy, Figure 2A). This is consonant with others' observations, which place the onset of hyponatremia approximately 7 days or even longer after receiving vincristine intravenously (7,9,16,48,49). We propose, as suggested elsewhere (17), that development of marked hyponatremia associated with vinca alkaloids definitely requires repeated administration of vincristine.…”
Section: Discussionsupporting
confidence: 91%
“…The first hyponatremic episode in our ALL cohort started on average between days 27 and 28 (average day 27.6) but occurred earlier or later in some patients (range from day 12 to day 39 after start of therapy, Figure 2A). This is consonant with others' observations, which place the onset of hyponatremia approximately 7 days or even longer after receiving vincristine intravenously (7,9,16,48,49). We propose, as suggested elsewhere (17), that development of marked hyponatremia associated with vinca alkaloids definitely requires repeated administration of vincristine.…”
Section: Discussionsupporting
confidence: 91%
“…14 This case report describes a patient who was diagnosed with ileus due to the interaction of VAs with posaconazole. Since Bohme et al 15 reported the first cases of paralytic ileus associated with VCR and itraconazole in four patients with ALL, there have been 15 additional cases of ileus due to VCR and itraconazole, 3 cases due to VCR and posaconazole, 2 cases due to VDS and itraconazole, and 1 case due to VCR and fluconazole published in PubMed [15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 2). The sex of 24 of these 25 patients was reported, and they comprised 14 male and 10 female patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vinca alkaloids, such as vincristine, induce hyponatremia through SIADH [145][146][147]. We should note that the simultaneous administration of vincristine with azoles is contraindicated, as the latter inhibit vincristine metabolism and, subsequently, may exacerbate the adverse effects of this drug, including neurotoxicity and hyponatremia [148,149]. CD19 + CAR T-cells used for the treatment of relapsed/refractory ALL may cause hyponatremia due to hypercytokinemia and elevated IL-6, which stimulates the hypothalamus for the inappropriate release of ADH [150].…”
Section: Hyponatremia Related To Pharmacological Agents Used In the Tmentioning
confidence: 99%